Dendroecology of Macrolobium acaciifolium (Fabaceae) in Central Amazonian floodplain forests - Batista, Eliane Silva; Schöngart, Jochen (Acta Amazonica, 2018)
The forest dynamics in the Amazonian floodplains is strongly triggered by the flood pulse. Trees respond to unfavorable growth conditions during the flood period by cambial dormancy, which results in the formation of annual growth rings. We determined tree age and compared the mean annual rates of increase in the diameter of Macrolobium acaciifolium with hydrological and climatic factors in three regions of central Amazonian floodplain forest. A wood sample was obtained from each tree using an increment borer. Ring growth was assessed by marginal parenchyma bands to determine tree age and the mean diameter increment. Ring widths were indexed to construct cross-dating chronologies and correlated with climatic and hydrological variables. The analyses demonstrate that the mean annual diameter increment did not differ between the three study sites. The chronologies correlated significantly with the terrestrial phase. There was no significant difference in the ring-width index between El Niño years and other years, and between La Niña and other years. These results show that the hydrological variables can be considered crucial to the rates of tree growth and diameter increment in floodplains, and El Niño signals were not detected in the tree-ring chronologies.
Dendroecologia de Macrolobium acaciifolium (Fabaceae) em florestas alagáveis da Amazônia central
Keywords: Tropical Forest; El Nino; Tree Rings; Dendroclimatology; Sea Surface Temperature; Florestas Tropicais; El Niño; Anéis De Árvores; Dendroclimatologia; Temperatura Da Surpefície Do Mar